Violence against women, Espírito Santo, Brazil - Franciele Marabotti Costa Leite; Maria Helena Costa Amorim; Fernando C Wehrmeister; Denise Petrucci Gigante
ABSTRACT OBJECTIVE To estimate the prevalence and factors associated with psychological, physical and sexual violence in women victims of intimate partner violence assisted in the primary care services. METHODS This is a cross-sectional study, conducted in 26 health units in Vitória, State of Espírito Santo, from March to September 2014. We interviewed 991 women aged 20-59 years. To classify the psychological, physical and sexual violence, the World Health Organization instrument on violence against women was used and a questionnaire to investigate the sociodemographic, behavioral characteristics, and the women's family and life history was developed. The statistical analyzes used were Poisson regression, Fisher's exact test and Chi-square. RESULTS The prevalence we observed were psychological 25.3% (95%CI 22.6-28.2); physical 9.9% (95%CI 8.1-11.9) and sexual 5.7% (95%CI 4.3-7.3). Psychological violence remained associated with education, marital status, maternal history of intimate partner violence, sexual violence in childhood and drug use, while physical assault was related to age, education, marital status and maternal history of intimate partner violence. Sexual violence occurred the most among women with low income, and victims of sexual violence in childhood. CONCLUSIONS Psychological, physical and sexual violence showed highly frequency among women assisted by primary care services. Sociodemographic and behavioral factors, personal experiences, and maternal violence influence the phenomenon.